Detection of Retinal Glial Cell Activation in Glaucoma by Time Domain Optical Coherence Tomography - Grieshaber, M. C.; Moramarco, F.; Schoetzau, A.; Flammer, J.; Orguel, S. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: Activated retinal astrocytes and Müller cells (ARAM) have been found in glaucoma patients. This study investigated whether presumed ARAM can be detected by optical coherence tomography (OCT), and assessed their relationship to the retinal nerve fiber layer (RNFL) thickness. Patients and Methods: Single-center observational study involving 35 age-matched healthy controls and 19 patients with primary open-angle glaucoma (POAG) between 45 − 82 years of age. Presumed ARAM was defined as patchy, discrete glittering but transparent changes of the macula. The retina was documented by red-free photography to assess distribution of ARAM, and compared to the RNFL thickness measured around the fovea by OCT. A linear mixed effects model was used to detect a difference between eyes with ARAM versus eyes without ARAM. Results: ARAM was not found in healthy subjects. The mean RNFL around the fovea was not significantly thicker in healthy controls (34.01 SD ± 22.24) than in POAG patients with ARAM (30.86 microns SD ± 15.09; p = 0.36) or without ARAM (33.19 microns SD ± 19.87; p = 0.46). Furthermore, the median RNFL thickness was similar to the control group (29 microns) but slightly thinner in POAG patients (each 27 microns with ARAM and without ARAM). In a subgroup analysis of POAG patients with ARAM, the within subject standard deviation of RNFL was significantly lower in areas with ARAM (SD 10.12) than in areas without ARAM (SD 17.30) (p < 0.001).Conclusions: Although the mean and median RNFL thickness was comparable between the groups, the variability of the RNFL thickness was significantly lower in areas with ARAM than in areas without ARAM suggesting that ARAM may mask RNFL loss in POAG patients.
Keywords: astrocytes; glaucoma; glial cells; intraretinal gliosis; Müller cells; retinal nerve fiber layer (RNFL) thickness; optical coherence tomography